TELAAH PROGRAM ZAKAT PRODUKTIF PADA BAITUL MAAL HIDAYATULLAH PERWAKILAN KALIMANTAN TIMUR - Nurwahyu, Nurwahyu; Haq, Nashirul (Asosiasi Dosen PTKIS Indonesia, 2022)
This study aims to find out about the management of productive zakat at BMH representatives of East Kalimantan, because the understanding of the community is still lay, in terms of empowerment, the welfare of mustahik through the distribution of productive zakat funds. The type of this research is a descriptive field research. In collecting data, researchers used interview techniques, as well as data analysis with data reduction, data display, and data verification or drawing conclusions. This study found that the productive zakat program at BMH East Kalimantan includes three things, namely fundraising, distribution and management. The collection carried out by BMH is not only from one source of funds but from various sources of funds. For distribution, what BMH does is distribute it to two groups, namely to people in need who do not have a previous business and who already have a business but need assistance from BMH to develop it. Then from its management, BMH helps from an economic perspective and helps muzakki to maintain their faith and worship to Allah, through evaluation and control meetings. The existing mechanism at BMH related to the productive zakat program is legally appropriate and does not violate the existing shari'a provisions, also the purpose of productive zakat is to develop and grow the economy for people in need, so that with the development of the economy, mustahiq no longer depend on other people for their lives.